الثقافة السياحية للمجتمع المحلي وانعكاساتها على السوق السياحية المحلية - ملاس, حسيبة (جامعة الوادي - University of Eloued, 2022)
ملخص: تمتلك الجزائر مؤهلات كبيرة تؤهلها إلى تصدر التصنيفات العالمية في مجال السياحة، ورغم ذلك فهي تشهد تراجعا واضحا في نشاط السوق السياحية، وإن كان البعض يرجع ذلك إلى غياب الإرادة السياسية الرشيدة والفاعلة للنهوض بقطاع السياحة، إلا أن المسألة في الحقيقة تتعدى ذلك إلى إشكالية وعي سياحي وثقافة سياحية، الأمر الذي انعكس بدوره على السوق السياحية، حيث جاءت هذه الورقة للبحث في هذا الموضوع، وقد تم اختيار مدينة حمام دباغ بولاية قالمة كميدان للدراسة؛ باعتبارها مجالا خصبا يعكس اهتمامات الموضوع. وباستخدام المنهج الوصفي ومنهج دراسة الحالة؛ وبالاستعانة بتقنية تحليل المضمون توصلت الدراسة إلى أن الثقافة السياحية للمجتمع المحلي لمدينة حمام دباع لها انعكاسات مباشرة على السوق السياحية المحلية، سواء بالسلب أو الإيجاب، وهذا متوقف على كيفية استغلالهم لرصيدهم من معارف ومهارات سياحية في تفعيل هذه السوق، وفي تأثير سلوكاتهم نحو السواح على نشاطها.Algeria possesses great qualifications to top international rankings in the field of tourism, and despite this it is witnessing a clear decline in the activity of the tourism market, although some attributed this to the absence of a rational and effective political will to promote the tourism sector, but the issue in fact goes beyond that to the problem of tourism awareness And a tourism culture, which was reflected in the tourism market, as this paper discusses this topic, and the city of Hammam Dabbagh in the Wilaya of Guelma was chosen as a fertile field of study that reflects the topic interests using the descriptive approach and the case study approach; with the assistance with a technic of content analysis, the study concluded that the tourism culture of the local community of Hammam Dubaagh has direct repercussions on the local tourism market, whether positively or negatively, and this depends on how they use their balance of tourism knowledge and skills in activating this market, and the effect of their behavior towards tourists on its activity.
مقال
Keywords: ثقافة محلية؛ سياحة محلية؛ تنمية؛ سائح؛ عرض وطلب; Local Culture- Local Tourism- Development–Tourist- Supply and Demand